2023
DOI: 10.1108/bij-06-2022-0355
|View full text |Cite
|
Sign up to set email alerts
|

Decoupling of a management standard: how decision-makers reinterpret, renegotiate, and modify the adoption of ISO 9001

Abstract: PurposeThe authors extend the literature on decoupling by analyzing the microlevel effects of institutionalized practices within the framework of international standards. This study investigates the specific informal management practices that decision-makers embrace in order for organizations to achieve ISO 9001 certification without all regulations being adopted and followed according to the standard's original design and purpose.Design/methodology/approachAs the basis for its research framework, this paper a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 69 publications
0
1
0
Order By: Relevance
“…Also in the case of international functioning the adoption of ISO 9001 certification is positively associated with exports (Yang et al, 2023). In another article, the authors indicated ambivalent behavior toward the ISO 9001 standard9s formal requirements (Georgiev, Georgiev, 2023). In turn, included in the latest version of the standard <risk-based thinking= was analyzed overall in QMS (Popova et al, 2019) or through am onsite management system audit (Naveen et al, 2022)…”
Section: Literature Review Resultsgeneral Approachmentioning
confidence: 99%
“…Also in the case of international functioning the adoption of ISO 9001 certification is positively associated with exports (Yang et al, 2023). In another article, the authors indicated ambivalent behavior toward the ISO 9001 standard9s formal requirements (Georgiev, Georgiev, 2023). In turn, included in the latest version of the standard <risk-based thinking= was analyzed overall in QMS (Popova et al, 2019) or through am onsite management system audit (Naveen et al, 2022)…”
Section: Literature Review Resultsgeneral Approachmentioning
confidence: 99%